Resources, services, and clientele of selected libraries of schools and colleges of music in Metro Manila access to music information - Santos, Florinda S.; Cruz, Ma. Divina P.; Nera, Fe Rosario C. (Quezon City Institute of Library Science, University of the Philippines Diliman, 2000)
This study is a survey of the existing information resources, services, clientele, equipment, facilities, and resource sharing activities of six selected libraries of schools and colleges of music in Metro Manila. It also seeks to determine the possibility of establishing a resource sharing program to improve access to music information among these respondent libraries.
The descriptive research method employing the questionnaire was used in this study. Personal interviews of the respondent librarians were conducted to verify the information gathered through the questionnaires. Documentary analysis were also utilized to obtain additional information on the existing information resources particularly important documents, e.g. reports, catalogs, and other materials.
The data gathered were systematically tallied and tabulated. Frequencies, percentages, and ranks were computed to analyze the data in accordance with the objectives of the study.
Among the major findings of the study were the following: 1) among the libraries surveyed, UP has the biggest number of collection and has the most number of library equipment; it is the largest in terms of physical facilities and has also the most number of professional and para-professional support staff; 2) telecommunication facilities are available in the respondent libraries in which an electronic exchange of information can be made possible; 3) three libraries are more advanced in equipping their libraries with the latest infrastructure in technology. 4) all libraries surveyed have organized collections; three libraries have strong Filipiniana vocal and instrumental music collections while the other three libraries are strong on foreign materials on music; 5) the resource sharing activities presently engaged in by the respondent libraries are: inter-library loan, exchange of publications, and photocopying services.
Results of the study revealed that an electronic exchangee of information is possible for the six institutions surveyed because of the availability of telecommunication facilities and the latest infrastructure in technology. Results further showed that the information resources, equipment, and facilities available in the six libraries surveyed are enough for initiating resource sharing activities.
Furthermore, the respondent libraries' positive attitude toward resource sharing activities is shown in their willingness to share staff and time for such activities.
Based on the above mentioned results, the study recommends the following: 1) in view of the increasing cost of library materials, increased users' demands, and technological advancements, there is a need for the six music school libraries surveyed to seek the support of their administrators in planning and implementing resource sharing programs and activities; 2) cooperative programs abd activities in which the libraries are willing to join in should be given priority in planning and implementation; 3) as far as information resources are concerned, there is an urgent need for the respondent libraries to update their library collections to find out their strengths and weaknesses and to determine which areas are to be given more attention; 4) there is an urgent need also for the six libraries surveyed to acquire more Filipiniana music materials through proper coordination with the National Commission for Culture and the Arts (NCCA) Committee on music to answer the users' information needs on Philippine music; 5) additional equipment and physical facilities among the libraries surveyed should be provided to further cope with increased users' demands and recent technological advancements; 6) with the available telecommunication facilities and the latest infrastructure in technology, an electronic exchange of information among the respondent libraries should dbe started; 7) a written formal policy regarding resource sharing activities should be drawn up to specify responsibilities among the participating libraries; 8)formulation of a continuing education program for both the professsional and para-professional support staff of the participating institutions to cope with the information and technological demands of the "New Millenium"; 9) Lastly, since one of the areas of concern of the NCCA Committee on Music is the dissemination of Philippine music through the "production of media and educational materials (recordings, books, monographs, and audio-visual materials)" (NCCA 1999:2), it is further recommended that an information linkage be established between the six respondent libraries and the above agency. This is also a way of realizing the Committee's vision of sustaining, enhancing, and developing the Filipino's national heritage as well as its rightful place in the global human community.
Computer print out.
Vita.
Special Problem (Master of Library Science)
Keywords: Library cooperation -- Philippines -- Manila Metropolitan Area; Music libraries -- Philippines -- Manila Metropolitan Area